Kamchatkan Volcanic Eruption Response Team (KVERT) Data in Internet - Girina O.A.; Romanova I.M. (Dalnauka, 2014)
KVERT IVS FEB RAS was founded in 1993. The goal of KVERT is to reduce the risk of aircraft encounters with volcanic ash clouds in the North Pacific region through timely detection of volcanic unrest, tracking of ash clouds, and prompt notification of airline authorities and others about volcanic ash hazards. KVERT staff work closely with staff of AVO, AMC (Airport Meteorological Center) at Yelizovo Airport and the Tokyo Volcanic Ash Advisory Center (VAAC), the Anchorage VAAC, the Washington VAAC, the Montreal VAAC and Darwin VAAC to release timely eruption warnings. KVERT staff analyzes volcano monitoring data (seismic (KB GS RAS), satellite, visual and video, and pilot reports), assigns a Aviation Color Code (ICAO) for aviation and issues reports on eruptive activity and unrest at Kamchatkan (since 1993) and Northern Kurile (since 2003) volcanoes. Since 1998 KVERT presented in Internet. Currently KVERT have a computer-aided web-system for preparing press-releases, mailing them to interested users and posting on KVERT site at web-server IVS (http://www.kscnet.ru/ivs/kvert). KVERT issues five types of VONA/KVERT releases about volcanic activity of Kamchatkan and Northern Kurile volcanoes: alerts when volcanic activity or an ash plume or an ash cloud are detected during last 6 hours; press-releases when the Aviation Color Code changes; Weekly Releases; Daily Report of volcanic activity detected during the last 24 hours UTC; Weekly Reports for Kamchatkan Branch of Russian Council Experts (http://www.kscnet.ru/ivs/kvert/van/). Basic information about the active volcanoes of Kamchatka and Northern Kuriles and their potential hazard to aviation are presented in the electronic catalogue at KVERT site: http://www.kscnet.ru/ivs/kvert/volcano.php?lang=en
Keywords: 20.23.17 Информационно-поисковые массивы. Базы данных. Манипулирование данными и файлами; 38.37.25 Вулканология